Longbone 검출기를 이용한 Scanogram의 유효성 평가 - 장수한(Jang Su-han), 허지은(Heo Ji-eun) (방사선기술과학, 2020)
Scanogram is that combine several practical images into one image to observation. So it is an important consideration in many clinical situation such as iliac measurement, leg alignment measurement and Scoliosis. Currently, scanogram examinations are mainly conducted for children and elderly patients. In this study, in order to apply the longbone detector to children or elderly patients who are difficult to cooperate with, we compared the longbone detector from D equipment with the G equipment discovery 656 Puls equipment in reproducibility of images, distribution of irradiation dose, scattering dose, irradiation time and image acquisition time. D equipment took more than twice as much time as G equipment. The scattered dose generated about 50% more G equipment than D equipment. In the whole spine scanogram and the measurement length of the lower leg, D equipment was also measured longer than G equipment. However, both methods did not show much difference from the CT scanogram, so there was no problem in measurement. The height of the thyroid radiation dose of G equipment was produced more radiation than D equipment. However, the longbone detector deviated from the x-ray center line relative to the tube rotation method, and was measured lower by the directionality of the measuring instrument, so that the error could not be corrected. In the conclusion of study, using the longbone detector is excellent for applying to children or elderly patients to reduce scattering dose. However, using CR may be useful to normal patients. Because, the image quality may deteriorate due to an imbalance of dose difference in thickness depending on the body part. So, it is useful to using a compensation filter or tube rotation method when we take a whole spine scanogram.